Intraocular lens optics and aberrations. Issue 4 (July 2016) - Chang, Daniel H.; Rocha, Karolinne M.
Abstract : Purpose of review: This review outlines concepts in intraocular lens (IOL) optics and aberrations important both for current IOLs and for new IOLs in development. Recent findings: Optical aberrations make a significant impact on the laboratory and clinical performance of IOLs, especially under mesopic and low-contrast conditions. Minimizing or correcting these aberrations can potentially improve visual function. Strategic management of aberrations can have clinical utility for extended depth of focus and presbyopia correction. Summary: All IOLs affect ocular aberrations in some manner. It is important for clinicians and researchers to understand the implications how any residual aberrations could affect visual quality, visual side-effects, and depth of focus.